Pathology Evaluation of Developmental Phenotypes in Neonatal and Juvenile Mice. Issue 3 (8th September 2017) - Bolon, Brad; Newbigging, Susan; Boyd, Kelli L.
Abstract: Necropsy (or autopsy) is the post mortem dissection of an animal to examine and collect organs and tissues in order to understand the effects and causes of disease. The systematic harvesting of samples at necropsy is an essential step in defining the reason for an unexpected death and in characterizing the features (i.e., phenotype) of a newly discovered condition. Phenotypic evaluation of young (neonatal and juvenile) mice emphasizes morphologic (macroscopic and microscopic) techniques and biochemical (clinical chemistry, hematologic, and molecular) analyses. This paper describes the most common procedures utilized to gather phenotypic data from neonatal and juvenile mice, with advanced alternatives for preparing special specimens (e.g., blood smears, electron microscopic samples). These techniques are applicable to young mice of all strains and are effective regardless of the fundamental cause, including genetically engineered or spontaneous mutations and exposure to pathogens or xenobiotic agents (i.e., foreign chemicals). © 2017 by John Wiley & Sons, Inc.